Ascertaining Association of Dermatoglyphic Pattern with Digits Using Correspondence Analysis Among Male and Female Convicted Prisoners - Jatinder Kaur; Maninder Kaur; Shriya Kalia (Brazilian Journal of Forensic Sciences, Medical Law and Bioethics, 2025)
The present study is an attempt to evaluate an association of dermatoglyphic pattern with digits among convicted male and female prisoners.  A total sample of 175 convicted prisoners (100 male and 75 female) and 175 controls (100 male and 75 female) ranging in age from 19 to 50 years was taken in the study. The data concerning fingerprints as well as criminal background of the prisoners was taken from different jails of Haryana (India). As per Henry’s system of fingerprint classification, ulnar loop was the most frequently occurring pattern followed by a whorl single spiral and a whorl double spiral in the left as well as right hand of both the convicted prisoners and control group of both the sexes. Dermatoglyphic patterns whorl concentric and accidental were completely absent among the female prisoner as well as control group. Correspondence analysis among convicted male prisoner group recorded a significant association of whorl double spiral with the digits L1 and R1 (thumb) in both the hands, while in control group the association of digits L1 and R1 (thumb) was found with loop ulnar. In the convicted female prisoner group, whorl double spiral exhibited an association with digit L1 and R1 (thumb), while the first digit (L1 and R1) was associated with lateral pocket loop in control counterparts. Further cross-sectional studies in this sphere are needed to establish these findings.